2018
DOI: 10.3389/fmicb.2018.00186
|View full text |Cite
|
Sign up to set email alerts
|

Resource Availability Drives Responses of Soil Microbial Communities to Short-term Precipitation and Nitrogen Addition in a Desert Shrubland

Abstract: Desert microbes are expected to be substantially sensitive to global environmental changes, such as precipitation changes and elevated nitrogen deposition. However, the effects of precipitation changes and nitrogen enrichment on their diversity and community composition remain poorly understood. We conducted a field experiment over 2 years with multi-level precipitation and nitrogen addition in a desert shrubland of northern China, to examine the responses of soil bacteria and fungi in terms of diversity and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 92 publications
16
65
0
Order By: Relevance
“…Forward selection revealed that the two kingdoms responded to different sets of soil physicochemical parameters, namely, bacterial community composition was affected by Ca and Mg, while fungal community composition was affected by Ca, Na, and K. These predictors are notably different from variables commonly accepted as important for microbial community composition, such as organic matter (46,47), pH (48,49), and N. The failure of organic matter and N to predict microbial community structure is surprising at first glance, given that scarce C and N availability can limit rates of microbial growth and functions such as mineralization and that the abundance of N-cycling microbial taxa often varies with C and inorganic N species. However, this result is consistent with multiple studies showing no effect of N on microbial community composition (50)(51)(52). Agricultural management might outweigh the effects of variation in these parameters since Ca and Mg were not affected by management.…”
Section: Discussionsupporting
confidence: 91%
“…Forward selection revealed that the two kingdoms responded to different sets of soil physicochemical parameters, namely, bacterial community composition was affected by Ca and Mg, while fungal community composition was affected by Ca, Na, and K. These predictors are notably different from variables commonly accepted as important for microbial community composition, such as organic matter (46,47), pH (48,49), and N. The failure of organic matter and N to predict microbial community structure is surprising at first glance, given that scarce C and N availability can limit rates of microbial growth and functions such as mineralization and that the abundance of N-cycling microbial taxa often varies with C and inorganic N species. However, this result is consistent with multiple studies showing no effect of N on microbial community composition (50)(51)(52). Agricultural management might outweigh the effects of variation in these parameters since Ca and Mg were not affected by management.…”
Section: Discussionsupporting
confidence: 91%
“…And the applied N significantly increased the inorganic N content in soil, which significantly effected on the bacterial and fungi communities ( Figure 5). Similar results were reported that the increase in N availability changed the microbial community (Fierer et al, 2007;She et al, 2018), and the soil nitrate N, SOC content, and organic C input environmental factors can be directly related to the mediated soilplant-microbe interaction (Zeng et al, 2016).…”
Section: Maintaining the Soil Microbial Community While Optimizing supporting
confidence: 85%
“…The nonsignificant water effects in our study were attributed to the finding that soil N availability was not affected by water addition (Figure 1b). Because the desert soil in our study contained only a small amount of organic matter (soil organic carbon content, 2.88 ± 0.18 g/kg; She et al, 2018), it is likely that water addition could not be enough to mineralize more available N from organic matter and thus could not enhance soil N availability (Wang et al, 2006). Alternatively, the simultaneous water addition with high natural precipitation in the present study may have led to soil N loss through leaching and denitrification (Huang, Yu, Li, Yuan, & Bartels, 2009;Srivastava, Singh, Tripathi, Singh, & Raghubanshi, 2018), resulting in no change in soil inorganic N availability.…”
Section: Discussionmentioning
confidence: 99%